Keanekaragaman Jenis Burung Di Lahan Basah Way Pegadungan Desa Rajawali Kecamatan Bandar Surabaya Kabupaten Lampung Tengah - Badia Roy Ricardo Nababan; Agus Setiawan; Nuning Nurcahyani (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Way Pegadungan wetlands is a wetland closure difference between the two riparian communities. One of the wetlands is converted into paddies fields, while the other is a natural wetland which are still overgrown with trees. To determine diversity differences in bird species between two wetlands research communities, the point count method (IPA) and line transects were used. Observations made by the stationary point count and record the birds found. Each community was taken 6 points count and observed for 3 days. Research encountered 41 species of birds included in the 17 families with a total of 796 individual in paddies fields and 46 birds species with total of 655 individuals from 17 families of individuals in natural wetlands. Natural wetlands diversity index was 3.44 with equality index of 0.90, this value is higher than the wetlands changed into paddies fields with a diversity index of 2.91, and in a stable condition with equality index of 0.78. Both wetlands communities have the same identical species approach (IS = 1) with a similarity index of 0.73. Keywords: birds, diversity, wetlands, Way Pegadungan